Complement Activation as a Helping Hand for Inflammophilic Pathogens and Cancer - Okrój, Marcin; Potempa, Jan (Frontiers in Immunology, 2019)
The complement system, an evolutionarily ancient component of innate immunity, is capable of protecting hosts from invading pathogens, either directly, by lysis of target cells, or indirectly, by mobilization of host immune mechanisms. However, this potentially cytotoxic cascade must be tightly regulated, since improperly controlled complement can damage healthy cells and tissues. The practical importance of this axis is highlighted when impairment of complement regulators or bacterial mechanisms of complement evasion result in pathogenic conditions. Recognition of complement as a “double-edged sword” is widely acknowledged, but another, currently underappreciated aspect of complement function has emerged as an important player in homeostatic balance – the dual outcome of complement-mediated inflammation. In most cases, the proinflammatory properties of complement are beneficial to the host. However, certain pathogens have developed the ability to utilize local inflammation as a source of nutrients and as a way to establish a niche for further colonization. Such a strategy can be illustrated in the example of periodontitis. Interestingly, certain tumors also seem to benefit from complement activation products, which promote a proangiogenic and immunosuppressive microenvironment.